2021
DOI: 10.23887/jpbi.v9i1.35049
|View full text |Cite
|
Sign up to set email alerts
|

Students and Parents’ Perceptions toward English Online Learning during Corona Virus Pandemic

Abstract: E-learning dramatically changes the learning process. As a result, both teachers and students have to work hard to adapt to the process. In response to these changes, this study aims to analyze the perceptions of junior high school, senior high school, and parents regarding online learning. This study involved 44 parents, 24 junior high school students, and 20 high school students. Data were collected using two questionnaires. The data collected were analyzed quantitatively in the form of percentages. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…(Lau, Li, & Lee 2021). However, Mongkaren et al (2021), revealed in their study that parents believed that traditional methods were more advantageous or successful than Internet learning. Additionally, because their children did not enjoy it, parents worried about their children's academic achievement and felt disconnected from their teachers due to online learning.…”
Section: Parents and Online Learningmentioning
confidence: 93%
“…(Lau, Li, & Lee 2021). However, Mongkaren et al (2021), revealed in their study that parents believed that traditional methods were more advantageous or successful than Internet learning. Additionally, because their children did not enjoy it, parents worried about their children's academic achievement and felt disconnected from their teachers due to online learning.…”
Section: Parents and Online Learningmentioning
confidence: 93%
“…The government was forced to enforce changes in learning modes as a form of prevention of the spread and transmission of the Covid-19 virus especially in higher education (Ferdianto & Dwiniasih, 2019;Lusiyani & Dara Anindya, 2021). In the end, the increasingly controlled rate of transmission of Covid-19 opened up the opportunity to carry out limited face-to-face learning, namely by the blended learning mode (Adnan, 2020;Liando et al, 2021). Blended learning is a strategic blend of face-to-face and online learning with the use of technology in it.…”
Section: Introductionmentioning
confidence: 99%
“…Technology in education is a system that is used to support learning so that the desired results are achieved (Liando et al, 2021;. The implementation of technology in education in Indonesia is that technology can be used as a learning media, administrative tool, and learning resource.…”
Section: Introductionmentioning
confidence: 99%